The Influence Of Marketing And Brand Of Bandung Tofu Nr (Nuri) On Purchase Decisions In Sadarkarya Village - Fahrozi, Ridwan; Gamiarci, Cici; Permasih, Desty (Management Science Doctoral Program, Pasundan University, 2024)
This research is a field research with a quantitative approach. Data collection techniques were carried out through questionnaires and Google Forms, while data analysis used quantitative methods that include data reduction, presentation, and drawing conclusions. Data were analyzed using multiple linear regression with the help of the SPSS version 20 application based on 97 respondents. The results showed that the independent variables, namely marketing influence and brand influence, simultaneously influenced purchasing decisions by 94.5%, while the remaining 5.5% were influenced by other variables. Hypothesis testing showed that marketing influence (X1) had a significance value of 0.000